Induced abortion: a cross-sectional study on knowledge of and attitudes toward the new abortion law in Maputo and Quelimane cities, Mozambique - Frederico, Mónica; Arnaldo, Carlos; Decat, Peter; Juga, Adelino; Kemigisha, Elizabeth; Degomme, Olivier; Michielsen, Kristien (BMC Women's Health, 2020)
Background: Maternal mortality, of which 6.7% is attributable to abortion complications, remains high in Mozambique. The objective of this paper is to assess the level of induced abortion at the community, as well as to assess awareness of and attitudes towards the new abortion law among women of reproductive age in suburban areas of Maputo and Quelimane cities. Methods: A cross-sectional household survey among women aged 15–49years in Maputo and Quelimane cities was conducted using a multi-stage clustered sampling design. Data on sociodemographic characteristics, maternal outcomes, contraceptive use, knowledge and attitudes towards the new abortion law were collected. Bivariate and multiple logistic regression analysis using the complex samples procedure in SPSS were applied. Results: A total of 1657 women (827 Maputo and 830 Quelimane) were interviewed between August 2016 and February 2017. The mean age was 27years; 45.7% were married and 75.5% had ever been pregnant. 9.2% of the women reported having had an induced abortion, of which 20.0% (17) had unsafe abortion. Of the respondents, 28.8% knew the new legal status of abortion. 17% thought that the legalization of abortion was beneficial to women’s health. Having ever been pregnant, being unmarried, student, Muslim, as well as residing in Maputo were associated with higher odds of having knowledge of the new abortion law. Conclusion: Reports of abortion appear to be low compared to other studies from Sub-Saharan African countries. Furthermore, respondents demonstrated limited knowledge of the abortion law. Social factors such as education status, religion, residence in a large city as well as pregnancy history were associated with having knowledge of the abortion law. Only a small percentage of women perceived abortion as beneficial to women’s health. There is a need for widespread sensitization about the new law and its benefits.
Keywords: Induced abortion; Abortion legislation; Women; Maputo; Quelimane; Knowledge